The effect of cultural adaptation on EFL reading comprehension: the role of narrative nativization and foreign language attitude - Mansoor Tavakoli; Salva Shirinbakhsh; Mohsen Rezazadeh (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This study examined the effect of cultural background knowledge on reading comprehension at inference and literal levels which was gained through reading an American short story that depicted either culturally familiar (nativized) or culturally unfamiliar (original) versions of the story. Subjects were intermediate level EFL learners studying English at a language institute in Iran. They answered true/false and multiple choice comprehension questions aimed at measuring the inference and literal comprehension over two versions of the story. They then completed a general attitude questionnaire showing their views toward nativization of short stories. Results revealed significant effect of cultural familiarity on inference and literal reading comprehension as well as negative attitude of Persian EFL learners toward nativized stories. Possible explanations are provided and the implications for the paradigm of English as an International Language are discussed.